Influence Of Low-Molecular Fraction (Up To 5 Kda) Of Human Cord Blood On Growth Properties Of Culture Of Mesenchymal Stromal Cells Subjected To Cryopreservation - Gulevsky, Oleksandr K.; Lavrik, Aleksey A.; Trifonova, Anna V.; Karpenko, Vladimir G. (Problems of Cryobiology and Cryomedicine, 2018)
The influence of cryopreservation on growth properties, immune phenotype and differentiation potential of mesenchymal stromal cells (MSCs) of human and rat was investigated, as well as the ability ofÂ human cord blood fractions below 5 kD (hCBF) to affect these indicesÂ in thawed cultures. It has beenÂ established that introduction of the hCBF with the concentration of 256-400 Âµg/ml to rat MSCs (rMSCs) culture caused the normalization of the cells growth properties reduced after cryopreservation that was not observed in human MSCs (hMSCs) culture. It has been shown that neither cryopreservation nor hCBF change the immune phenotype and ability for multi-lineage differentiation of hMSCs and rMSCs. The efficiencyÂ of low molecular weight fraction dependent on physiological characteristics of cells and its concentration in culture medium was concluded. Probl Cryobiol Cryomed 2018; 28(2): 131â€“138